“We Speak for Those who Cannot Speak for Themselves”: The Toronto Humane Society, 1887-1891 - Woodger, Kevin (Ontario History, 2013)
This article examines the history of the Toronto Humane Society [THS] from 1887 to 1891. It argues that the THS drew on the discourses of earlier Humane Societies and SPCAs in Britain and the United States and concludes that, like other animal welfare organizations, the THS saw the moral reform of the working classes as one of its primary duties. To do this, the Humane Society is linked to the larger moral and social reform movement that permeated the city in the late-nineteenth century. Dominated by members of Toronto’s middle class, the THS inordinately targeted workers in its efforts to spread humane sentiments throughout the city.